Risk factors for sexual assault and sexual harassment in the U.S. Military findings from the 2014 RAND Military Workplace Study - Schell, Terry L. 1967-; Morral, Andrew R.; Cefalu, Matthew; Farris, Coreen; Matthews, Miriam (RAND, 2021)
This report describes analyses designed to identify service member and environmental characteristics that are associated with service members' risk of sexual assault or sexual harassment. The researchers find that experiencing pre-service sexual assault, being younger, and being single were all strong predictors of experiencing sexual assault and sexual harassment. Service history and unit environment characteristics were also associated with risk, although these effects were smaller. Risk factors for men and women and for sexual assault and sexual harassment were strongly correlated, suggesting that a common set of risk factors underlie these experiences for men and women. The authors conclude the report with recommendations for how the Department of Defense (DoD) can use the findings to modify programs and training that address sexual assault and sexual harassment. Data for these analyses were drawn from the 2014 RAND Military Workplace Study, an independent assessment of sexual assault and sexual harassment in the U.S.
Keywords: USA -- Army; Sexuelle Belästigung; Rape in the military / United States; Sexual harassment in the military / United States; Soldiers / Crimes against / United States